-6(x+3)+4x+7=6x+8

Simple and best practice solution for -6(x+3)+4x+7=6x+8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(x+3)+4x+7=6x+8 equation:


Simplifying
-6(x + 3) + 4x + 7 = 6x + 8

Reorder the terms:
-6(3 + x) + 4x + 7 = 6x + 8
(3 * -6 + x * -6) + 4x + 7 = 6x + 8
(-18 + -6x) + 4x + 7 = 6x + 8

Reorder the terms:
-18 + 7 + -6x + 4x = 6x + 8

Combine like terms: -18 + 7 = -11
-11 + -6x + 4x = 6x + 8

Combine like terms: -6x + 4x = -2x
-11 + -2x = 6x + 8

Reorder the terms:
-11 + -2x = 8 + 6x

Solving
-11 + -2x = 8 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
-11 + -2x + -6x = 8 + 6x + -6x

Combine like terms: -2x + -6x = -8x
-11 + -8x = 8 + 6x + -6x

Combine like terms: 6x + -6x = 0
-11 + -8x = 8 + 0
-11 + -8x = 8

Add '11' to each side of the equation.
-11 + 11 + -8x = 8 + 11

Combine like terms: -11 + 11 = 0
0 + -8x = 8 + 11
-8x = 8 + 11

Combine like terms: 8 + 11 = 19
-8x = 19

Divide each side by '-8'.
x = -2.375

Simplifying
x = -2.375

See similar equations:

| T=4U/E | | -3-p=5p+21 | | X^2-3ax+2a^2+3a-9=0 | | 5a+b=cfora | | T=AB-2 | | 9x-8+9x=7x+16 | | -x+4x+6=14-2 | | 58a+b=cfora | | 13x-3=5x | | 2b-3+6-8=1-b | | x/(x+1)+x/(x-1)=0 | | 2x/5+3=101/2 | | 4m-y=nform | | 12+4x=8x-8 | | 1/2(8-6h)=5 | | 3x^2-12x+24y-48=0 | | 6-4x=7x-9x+4+2 | | C=15f+8h+5p | | 27x-2+47=180 | | 4z+6z=10 | | 27x-2=47 | | 4(x-3)+2=26 | | 7m+n=2forn | | 16x-8=14x+8 | | -3-(2-3x)=2x-(5-x) | | (3x-c)-5=x-7 | | 13-2n=-37 | | a+b(x-y)=cforx | | 20x+10=50 | | 2(x+4)-5(2x-1)= | | 11x-3=10x+5 | | n^2+n=6 |

Equations solver categories